Implementing culturally competent transplant care and implications for reducing health disparities: A prospective qualitative study. (9th October 2020) - Gordon, Elisa J.; Romo, Elida; Amórtegui, Daniela; Rodas, Alejandra; Anderson, Naomi; Uriarte, Jefferson; McNatt, Gwen; Caicedo, Juan Carlos; Ladner, Daniela P.; Shumate, Michelle
Abstract: Background: Despite available evidence‐based interventions that decrease health disparities, these interventions are often not implemented. Northwestern Medicine's ® Hispanic Kidney Transplant Program (HKTP) is a culturally and linguistically competent intervention designed to reduce disparities in living donor kidney transplantation (LDKT) among Hispanics/Latinos. The HKTP was introduced in two transplant programs in 2016 to evaluate its effectiveness. Objective: This study assessed barriers and facilitators to HKTP implementation preparation. Methods: Interviews and group discussions were conducted with transplant stakeholders (ie administrators, nurses, physicians) during implementation preparation. The Consolidated Framework for Implementation Research (CFIR) guided interview design and qualitative analysis. Results: Forty‐four stakeholders participated in 24 interviews and/or 27 group discussions. New factors, not found in previous implementation preparation research in health‐care settings, emerged as facilitators and barriers to the implementation of culturally competent care. Implementation facilitators included: stakeholders' focus on a moral imperative to implement the HKTP, personal motivations related to their Hispanic heritage, and perceptions of Hispanic patients' transplant education needs. Implementation barriers included: stakeholders' perceptions that Hispanics' health insurance payer mix would negatively impact revenue, a lack of knowledge about LDKT disparities and patient data disaggregated by ethnicity/race, and a perception that the family discussion component was immoral because of the possibility of coercion. Discussion and Conclusions: Our study identified novel barriers and facilitators to the implementation preparation of a culturally competent care intervention. Healthcare administrators can facilitate organizations' implementation of culturally competent care interventions by understanding factors challenging care delivery processes and raising clinical team awareness of disparities in LDKT.